A Promotive Process of Resource Gain Against Harsh and Inconsistent Discipline in Mothers Coping With Breast Cancer: A Serial Mediation Model - Zamir, Osnat; Bentley, Gabriella; He, Yaliu (Frontiers in Psychiatry, 2022)
Breast cancer is a life-threatening disease and a source of enduring stress. The Family Stress Model posits that psychological distress provoked by stressful conditions may spill over and intensify harsh and inconsistent parental discipline. However, the Conservation of Resources theory posits that having more resources may lead to further resource gain, which may promote adaptive coping with adversities. Therefore, this study examined a serial mediation model in which financial resources (income) are predicted to be associated with more interpersonal resources (paternal involvement). The latter is expected to be linked with less maternal post-traumatic stress symptoms, which, in turn, should be associated with less harsh and inconsistent discipline in mothers coping with breast cancer. A sample of 100 Israeli mothers receiving breast cancer treatments was recruited through social media. The participants completed online self-report questionnaires. Structural Equation Modeling indicated significant serial mediation, in which a greater income level was associated with more paternal involvement, which was linked to a lower level of maternal post-traumatic symptoms. The latter, in turn, was associated with less harsh and inconsistent maternal discipline practices. We controlled for illness severity and the time since diagnosis, which did not predict maternal discipline practices. The study suggests that although breast cancer is a stressful condition for any family, having more financial resources can be a significant promotive factor predicting a cascading process by which paternal functioning facilitates better mental health of mothers, and, in turn, better maternal parenting practices.